2011
DOI: 10.1097/hmr.0b013e3181fb0f2b
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals' health promotion services in their communities

Abstract: Collaboration and linkages with other organizations enable hospitals to expand HP. Hospitals should apply management methods (not just HP methods) to effectively offer HP services. Support for small hospitals' HP is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This finding was confirmed by Swedish authors, who also concluded that the management has a major role in creating opportunities for health professionals to participate in HP activities (Johansson et al, 2010). In a systematic review of HP services provided by the US hospitals in their communities, Olden and Hoffman (Olden and Hoffman, 2011) also concluded that hospitals should apply management methods to effectively introduce HP services.…”
Section: Discussionsupporting
confidence: 63%
“…This finding was confirmed by Swedish authors, who also concluded that the management has a major role in creating opportunities for health professionals to participate in HP activities (Johansson et al, 2010). In a systematic review of HP services provided by the US hospitals in their communities, Olden and Hoffman (Olden and Hoffman, 2011) also concluded that hospitals should apply management methods to effectively introduce HP services.…”
Section: Discussionsupporting
confidence: 63%
“…However, the authors' findings that hospital size and collaborative networks were positively associated with more community programs and that state community benefit laws had no association with programs continue to be relevant. However, the concepts of evaluation or impact were not raised anywhere in the review (73). A literature review by Burke et al showed that out of 106 programs that met inclusion criteria, over half occurred in the hospital facility and focused on clinical interventions (28).…”
Section: Community Programsmentioning
confidence: 99%
“…In many health promotion programs implemented in hospitals, the community needs assessment is one of the preparatory measures ( 16 ). Other health promotion projects for implementing health promotion programs in the hospitals focus on managerial methods, sharing and using resources ( 17 ), and collaboration with society organizations ( 18 ). Finally, many hospitals in the world have implemented the WHO HPH program and have achieved cost-effectiveness and quality assurance of health services ( 19 20 ).…”
Section: Introductionmentioning
confidence: 99%